Protein Adsorption on Modified Bacterial Cellulose - Piluharto, Bambang; Sulistyowati, Fitri; Indarti, Dwi; Busroni, Busroni (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2020)
The protein adsorption was interesting study, especially in the biological fluidic application. In the present study, we study the protein adsorption behavior on the bacterial cellulose and modified bacterial cellulose. In here, bacterial cellulose was modified by acid hydrolysis using hydrochloric acid. The contact time and pH were used as variable to study protein adsorption behavior on the modified bacterial cellulose. As the results, based on functional group analysis, there are not different between bacterial cellulose and modified bacterial cellulose. However, after modification, there was increasing of crystallinity of bacterial cellulose from 84.5% to be 87.7%. In the protein adsorption study, increasing the contact time increase percent adsorption until contact time of 90 minutes, however the further contact time relatively constant. The protein adsorption on both of bacterial cellulose and modified bacterial cellulose decreases, following the increase of pH.